2021
DOI: 10.3390/agriculture11060483
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Addition to Soil Improves Seed Yield, Foliar Stomatal Conductance, and the Photosynthetic Response of Rapeseed (Brassica napus L.)

Abstract: The effects of nitrogen and phosphorus levels on the physiological traits, yield, and seed yield of rapeseed (Brassica napus L.), were studied in a farm research project of Zanjan University. Three levels of nitrogen (0, 100, and 200 kg/ha) and three levels of phosphorus (0, 75, and 150 kg/ha) were considered. The results showed that an increase in nitrogen level caused an increase in the leaf chlorophyll content so that the application of 200 kg/ha of nitrogen increased the chlorophyll content of the leaves u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…Liming has also been linked to an increase in crop yields [52,53]. In addition, interactive effects of N and P fertilizers increases chlorophyll content, stomatal conductance and quantum yield of photosystem II resulting in higher yield of crops [54]. Crop yields of straw likewise followed a similar pattern.…”
Section: Discussionmentioning
confidence: 94%
“…Liming has also been linked to an increase in crop yields [52,53]. In addition, interactive effects of N and P fertilizers increases chlorophyll content, stomatal conductance and quantum yield of photosystem II resulting in higher yield of crops [54]. Crop yields of straw likewise followed a similar pattern.…”
Section: Discussionmentioning
confidence: 94%
“…The results of soil samples analysis of the natural habitats of FG in the Zanjan Province are presented in Table 4. Soil texture characteristics (amount of clay, sand and silt) and elements concentration in the soil (amount of potassium and nitrogen) are important and influential factors on FG distribution as observed by other authors [22,24,26]. The structure of the soil with its vegetation influences the amount of humidity and plant elements available, the water retention capacity and permeability of the soil, the organic matter present, the nutrient cycle of the soil and the depth of rooting of the plants.…”
Section: Soilmentioning
confidence: 84%
“…The distribution of plant species in rangeland ecosystems is not accidental; rather, environmental factors such as climate, soil, topography and human activities play an important role in the expansion of plants [17,18]. Some authors have shown that the establishment of plant communities in mountainous areas is mainly affected by climate factors, and in low-lying areas and rolling hills by soil factors [19][20][21][22][23]. Therefore, it seems that regarding the establishment of FG in the highlands, climatic factors have the greatest role in the distribution and establishment of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of practices such as split application and sowing fertilization can increase the efficiency of nitrogen use by up to 16-17% in calcareous soils [50]. A higher level of available nitrogen in calcareous soil results in a higher yield of plants, even in semi-dry soil conditions [51]. The small granules of U-PSf can be recommended for these conditions with a high dissolving capacity.…”
Section: Discussionmentioning
confidence: 99%